A novel molecular carrier from Newcastle Disease Virus. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2003)
Various kinds of carrier molecules have been used to deliver nucleic acids, drugs. vaccines and other important compounds. A molecular carrier for immunogenic peptides has been developed which can be used for the development of multicomponent vaccines. diagnostic reagents and the delivery of novel therapeutics or drugs. It has been discovered that the nucleocapsid protein of a local Malaysian poultry virus (Newcastle disease virus) produced in Escherichia coli assembles into ring-like and herringbone-like particles. It is possible to manipulate the lengths of these particles by genetically engineering one end of this nucleocapsid protein.